BMI-Specific Waist Circumference Thresholds to Discriminate Elevated Cardiometabolic Risk in White and African American Adults - Amanda E. Staiano; Claude Bouchard; Peter T. Katzmarzyk (Obesity Facts, 2013)
Objective: Waist circumference (WC) is a useful anthropometric tool to estimate cardiometabolic risk. However, BMI influences the relationship between WC and health. This study determined BMI-, sex- and race-specific WC thresholds. Methods: The study sample included 6,452 whites and African Americans (AA) aged 18-64 years. WC, BMI, and cardiovascular risk factors were assessed in the clinic. An elevated cardiometabolic risk was defined as the presence of ≥2 cardiometabolic risk factors. Receiver Operating Characteristic (ROC) curves were used to determine BMI-, sex-, and race-specific WC thresholds. Results: Based on logistic regression, elevated WC within each BMI category was associated with higher cardiometabolic risk. The respective optimal BMI-specific WC thresholds for white women, AA women, white men, and AA men were as follows: 72, 76, 82, and 78 cm for normal-weight (18.5-24.9 kg/m2); 87, 85, 95, and 92 cm for overweight (25-29.9 kg/m2); 97, 97, 107, and 104 cm for obese I (30-34.9 kg/m2); and 111, 110, 120, and 119 cm for obese II+ (≥35 kg/m2) participants. Sensitivities ranged from 52.7 to 73.3%, and specificities ranged from 57.1 to 73.5%. Conclusion: The proposed optimal BMI-, sex-, and race-specific WC thresholds are warranted for use in the clinical setting until representative standards become available based on results from longitudinal studies.